2017
DOI: 10.1007/s10552-017-0998-4
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban differences in surgical treatment, regional lymph node examination, and survival in endometrial cancer patients

Abstract: Future research should continue to assess the association between access to care and disparities in surgical care and the effect of these disparities on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…This includes comorbidities, psychological distress, and lower levels of physical activity [19, 20]. A recent study observed significantly increased risk of death in rural endometrial cancer patients compared to urban patients, however they were not able to include BMI and baseline health which we included [11]. Generally, in our study rural endometrial cancer patients had higher rates of multiple comorbidities.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This includes comorbidities, psychological distress, and lower levels of physical activity [19, 20]. A recent study observed significantly increased risk of death in rural endometrial cancer patients compared to urban patients, however they were not able to include BMI and baseline health which we included [11]. Generally, in our study rural endometrial cancer patients had higher rates of multiple comorbidities.…”
Section: Discussionmentioning
confidence: 86%
“…This may be a result of reduced access to healthcare. Patients in rural areas are likely to live much farther from a cancer center and may have less access to adjuvant therapy, which has been associated with decreased survival [11, 21]. Patients may also be offered therapy, but may decline it due to reasons such as distance and cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is often influenced by patient characteristics such as age, comorbidities and patient preference. Furthermore, the type of treatment centre (cancer centre or smaller hospital) also influences the type of treatment offered to patients and influences survival in endometrial cancer patients [35,36]. Patients with low SES are less likely to afford travel costs to cancer centres, especially if they reside in rural counties.…”
Section: Discussionmentioning
confidence: 99%